STUDENTS’ PERCEPTIONS TOWARD THE USE OF GRAMMARLY AS A GRAMMAR CHECKER IN THE PROCESS OF WRITING - Yurika, Fatma; Munir, Munir; Farahdiba, Syarifah (Universitas Negeri Makassar, 2022)
The purpose of this study was to find out how students perceive the use of Grammarly Premium in the process of writing. This research applied the qualitative method to achieve the research objectives. The subjects of this research were 6 students from the English Education Department, Faculty of Languages and Literature, Universitas Negeri Makassar, who are currently in their seventh semester of the academic year 2022/2023, The subjects were chosen by using purposive sampling. This research used the interview as the instrument of the study. The findings of this research found that students perceive positive and negative perceptions toward the use of Grammarly Premium. Positive perceptions include being easy to access and use having more complete features, can be integrated into the laptop software, motivating, and having a lot of useful features. Negative perceptions include less accurate and detailed feedback, sometimes feedback out of context, limited plagiarism feature, and requires a stable internet connection. The result showed that students’ perceptions were dominated by positive perceptions.